Investigation on oral healthy literacy among college students in Tongliao, Inner Mongolia, China (内蒙古自治区通辽市地区大学生口腔健康素养状况调查与分析) - DENG Jiazheng (邓家峥); HONG Yan (洪艳); HAN Rui (韩蕊) (中西医结合护理)
Objective To investigate the status quo of oral healthy literacy (OHL) among college students in Tongliao City, Inner Mongolia, and explore its influencing factors. Methods The students of Inner Mongolia Minzu University were selected as the research objects by convenient sampling method. General data questionnaire and oral health literacy scale were used to investigate them. Results A total of 501 college students were recruited in the questionnaire survey. The average OHL score of college students was (338. 15±57. 61), ranged from 121 to 441, and scores of each dimension were as follows: Information-related ability (119. 09±19. 78), health maintenance ability (78. 32±15. 72), personal characteristics (77. 79±14. 94), social support (35. 53±7. 27), basic skills (27. 43±9. 46). The results of univariate analysis showed that there were significant differences between low OHL and high OHL in household registration, whether they were engaged in the medical/academic/health industry, and whether their friends had or were currently suffering from oral diseases (P＜0. 05). Results of multi-factor analysis showed that whether engaged in medical and health industry/education/health industry had significant independent influence on OHL of college students (P＜0. 05). Conclusion The OHL of college students was in the middle level, and it is necessary to add health-related general courses in personnel training programs to comprehensively enhance students' oral health awareness and ability, and improve their overall health level. (目的 了解内蒙古自治区通辽市地区大学生口腔健康素养(OHL)现状, 并探讨其影响因素。方法 采用便利抽样法, 选取内蒙古自治区通辽市内蒙古民族大学在校生为研究对象。采用一般资料调查表、OHL量表对其进行调查。结果 共501名在校生参与调查。内蒙古自治区通辽市地区大学生OHL量表综合评分121～441分, 平均(338. 15±57. 61)分; 各维度得分由高到低分别为: 信息相关能力(119. 09±19. 78)分、健康维持能力(78. 32±15. 72)分、个人特征(77. 79±14. 94)分、社会支持(35. 53±7. 27)分、基本技能(27. 43±9. 46)分。单因素分析显示, 低OHL和高OHL的在校生在户口所在地、是否从事医疗卫生行业/学业/健康产业、是否朋友曾经患过或现在患有口腔类疾病方面比较, 差异有统计学意义(P＜0. 05); 多因素分析显示, 是否从事医疗卫生行业/学业/健康产业是OHL的独立影响因素(P＜0. 05)。结论 内蒙古自治区通辽市地区大学生的OHL处于中等水平。需在人才培养方案中增设健康相关的通识课程, 全面增强学生的口腔健康意识与能力, 提升大学生整体健康水平。)